The polarity of wisdom and fear of God in the Eden narrative and in the Book of Proverbs - Forṭi, Ṭovah ca. 20./21. Jh. (2011)
Wisdom’s presence throughout creation giving pleasure to her divine Father / guardian (Prov. 8:30) in primordial time, puts her in a preeminent position between man and God. My discussion of the motif of eating from the tree of knowledge in the Garden of Eden through the wisdom perspective of Proverbs adds a further conceptual stratum for evaluating the interrelation between the values of faith and intellect.
Wenn die Weisheit, die ihren Vater / Beschützer in uranfänglicher Zeit erfreut (Prov 8,30), während der Schöpfung anwesend ist, verleiht ihr dies eine herausragende Stellung zwischen Mensch und Gott. Meine Diskussion des Motivs des Essens vom Baum der Erkenntnis unter weisheitlichem Blickwinkel lässt für eine Einschätzung des Zusammenhangs intellektueller und glaubensorientierter Werte eine weitere konzeptionelle Schicht sichtbar werden.
Keywords: Bibel; Bibel; Bibel; Weisheit; Gottesfurcht